Improved field-portable system to measure Cs-137 in wildlife. (November 2020) - Whiteside, Tad S.; Brand, Alexander D.; Aucott, Timothy J.; DiPrete, David P.
Abstract: We have developed an improved system to measure Cs-137 in wildlife at the Savannah River Site. This field-portable system consists of a shielded 5 cm by 10 cm by 40 cm NaI detector controlled by an Ametek Ortec Digibase. Measurement of an animal's radioactivity is made by placing the animal at a predefined location on the detector system for a one minute count-time. The counts, animal type, and animal weight are then used as inputs to an algorithm which calculates the amount of Cs-137 within the whole animal and within the edible meat portion of the animal. The results from these calculations are used to estimate the received dose from eating this animal and is included in the Savannah River Site's Hunter Dose Tracking System. This system has a detection limit of 0.60 pCi/g (22.20 Bq/kg) with a typical measurement uncertainty of less than 0.32 pCi/g (11.84 Bq/kg). Graphical abstract: Highlights: Using a MCNP-derived algorithm and a large, shielded detector increases accuracy. An on-board check-source prevents unwanted drift and reduces uncertainty. Understanding which parts of the body contain Cs-137 increases accuracy.